PENGARUH FINANCIAL LITERACY TERHADAP KEPUTUSAN INVESTASI GENERASI MILENIAL DI KOTA PONTIANAK - reni helvira (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to determine the effect of literacy on investment decisions in the millennial generation in Pontianak City. Based on the results of the study indicate that the value of the regression equationis Y = 2.210 + 0.521X. The value of the simple correlation coefficient (r) is 0.633 which means the relationship/correlation between financial literacy on decisions Pontianak's millennial generation investment is strong. The value of the coefficient of determination (R2) obtained is equal to 0.400, meaning the influence of financial literacy on variations in the ups and downs of millennial generation investment decisions in the City Pontianak is 40.00%, and the remaining 60.00% is influenced by other variables outside of this study. The results of the Simultaneous Test (Test F) show the value of 65.383 (F count) > 3.94 (F table) with a significance value of F which is 0.000 which value is less than 0.05. This means that a simple regression model can used to predict the investment decisions of the City's millennial generation Pontianak which is influenced by financial literacy. Partial Test Results (t Test) shows the value of t count > table (8.086 > 1.98), so Ho is rejected and Ha accepted which means that there is a positive and partially significant effect between financial literacy variables on millennial generation investment decisions Pontianak City. Keywords: Financial Literacy, Investment, Millennials